Die invloed van emosies op gebeure in die Matteus-evangelie - D A Pauw (Acta Theologica)
Emotions are experienced by every human being. Decisions and actions are inevitably influenced by these emotions. The course of history is therefore, to a greater or lesser extent, determined by emotions of individual decision makers, of groups or of crowds. Some introductory remarks on the nature and effect of emotions are followed by an analysis of emotions featuring in Matthew's account. Anger at, as well as the anger of Jesus figures prominently; despondency makes people turn to Jesus for help; fear may have the beneficial effects and often becomes instrumental in the execution of God's plan; hatred and scorn have negative and even fatal consequences; dismay renders crowds susceptible to the message of salvation. Of all the role players Jesus is the one whose emotions feature most prominently. The anti-Jesus factions are goaded on by their intense emotions to negative onslaughts, which Jesus, however, transforms into positive opportunities for admonishing and educating his audience. It is notable that human emotions become instrumental in the fulfilment of prophecies and in the execution of God's plan. Emotions play a determining role in decisions for or against Jesus, and it is emotions that cause people to witness, to worship and to praise the Lord. By means of the frequency and intensity of Jesus' emotions, the completely human side of his nature is irrefutably revealed. It is inevitable that the analysis of the role of emotions in the Gospel according to Matthew, will and should have practical implications for present-day believers.